South and Southeast Asia Workshop for Nagoya Protocol and Plant Treaty National Focal Points, 27-30 March 2017, International Rice Research Institute Los Baños, the Philippines - Gullotta, Gaia; Halewood, Michael; Sackville-Hamilton, N. Ruaraidh; Drews, Andreas; Garforth, Kathryn; Nnadozie, Kent (Bioversity International, 2021)
This report documents the South and Southeast Asia Workshop for Nagoya Protocol and Plant Treaty National Focal Points, which took place from 27-30 March 2017 at the International Rice Research Institute in Los Baños, the Philippines.